The information content of central bank interest rate projections: Evidence from New Zealand - Gunda-Alexandra Detmers; Dieter Nautz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
The Reserve Bank of New Zealand (RBNZ) has been the first central bank that began to publish interest rate projections in order to improve its guidance of monetary policy. This paper provides new evidence on the role of interest rate projections for market expectations about future short-term rates and the behavior of long-term interest rates in New Zealand. We find that interest rate projections up to four quarters ahead play a significant role for the RBNZs expectations management before the crisis, while their empirical relevance has decreased ever since. For interest rate projections at longer horizons, the information content seems to be only weak and partially destabilizing.
Keywords: E52; E58; 330; central bank interest rate projections; central bank communication; expectations management of central banks; Geldpolitik; Informationsverhalten; Zentralbank; Staatliche Information; Zins; Prognose; Neuseeland